Problem No. 46

Algebra Level 3

If x = 2013 y z , y = 2014 z x x=\sqrt{2013-yz}, y=\sqrt{2014-zx} and z = 2015 x y , z=\sqrt{2015-xy}, find ( x + y ) 2 + ( y + z ) 2 + ( z + x ) 2 (x+y)^{2}+(y+z)^{2}+(z+x)^{2}


The answer is 12084.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

From the hypothesis, we get x 2 + y z = 2013 ; y 2 + x z = 2014 ; z 2 + x y = 2015 x^2+yz=2013; y^2+xz=2014; z^2+xy=2015 .

Thus,

( x + y ) 2 + ( y + z ) 2 + ( z + x ) 2 \quad(x+y)^2+(y+z)^2+(z+x)^2

= 2 ( x 2 + y 2 + z 2 + x y + y z + z x ) =2(x^2+y^2+z^2+xy+yz+zx)

= 2 ( 2013 + 2014 + 2015 ) = 12084 =2(2013+2014+2015)=\boxed{12084} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...